Knowledge platform affordances and knowledge collaboration performance: The mediating effect of user engagement - Jiao, Zeyu; Li, Chang; Chen, Jianbin (Frontiers in Psychology, 2022)
Knowledge collaboration is the result of knowledge transfer and social interaction among users on knowledge platforms, and its formation mechanism has attracted much attention. Based on the affordance theory, this paper introduces user engagement as a mediating variable to study the relationship between knowledge platform affordances and knowledge collaboration performance. Data collected from 361 valid questionnaires from the Zhihu platform were analyzed by using SPSS 26.0 and Amos 24.0. The results show that knowledge platform affordances have a direct and positive influence on knowledge collaboration performance as well as an indirect influence through user engagement. Expressly, user engagement undertakes three intermediary paths between knowledge platform affordances and knowledge collaboration performance: knowledge affordances-conscious participation-knowledge collaboration performance, knowledge affordances-enthusiasm-knowledge collaboration performance, and social affordances-social interaction-knowledge collaboration performance. This paper explores the formation process of knowledge collaboration performance by synthesizing affordance and user engagement theories. It clarifies the fundamental role of knowledge affordances in stimulating users’ conscious participation and enthusiasm, and the critical role of social affordances in stimulating social interaction. Therefore, this paper further enriches theories of knowledge collaboration and knowledge platform affordances and provides a practical reference for the strategic optimization and development of knowledge platforms.